2016
DOI: 10.1111/maec.12268
|View full text |Cite
|
Sign up to set email alerts
|

Alien biodiversity in Mediterranean marine caves

Abstract: The number of alien species in the Mediterranean Sea is increasing rapidly, but few attempts have been made to evaluate impacts on specific habitat types. The present study investigated alien biodiversity in Mediterranean marine caves, both by contributing new records of Eastern Mediterranean cave aliens, and by reviewing the scattered existing literature; the main goals were to highlight potential impacts and investigate the importance of cave environments for the expansion of alien species. Seven new alien s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 50 publications
4
41
0
Order By: Relevance
“…Studies in the southeastern Mediterranean basin have brought to light a considerable number of NIBs (Harmelin 2014b, Gerovasileiou et al 2016, Harmelin et al 2016, Sokolover et al 2016), mainly originated from the Red Sea/Indo-Pacific Ocean. Until today, 12 NIBs have been reported from the Greek seas, representing 5% of the bryozoan fauna of Greece and 20% of the Mediterranean NIB fauna; these are the ctenostomes Amathia gracillima and A. verticillata and the cheilostomes Bugula neritina , Bugulina fulva , Crepidacantha poissonii , Crisularia plumosa , C. serrata , Exechonella antillea , Hippopodina feegeensis , Microporella coronata , Parasmittina raigii , and Scrupocellaria scruposa .…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the southeastern Mediterranean basin have brought to light a considerable number of NIBs (Harmelin 2014b, Gerovasileiou et al 2016, Harmelin et al 2016, Sokolover et al 2016), mainly originated from the Red Sea/Indo-Pacific Ocean. Until today, 12 NIBs have been reported from the Greek seas, representing 5% of the bryozoan fauna of Greece and 20% of the Mediterranean NIB fauna; these are the ctenostomes Amathia gracillima and A. verticillata and the cheilostomes Bugula neritina , Bugulina fulva , Crepidacantha poissonii , Crisularia plumosa , C. serrata , Exechonella antillea , Hippopodina feegeensis , Microporella coronata , Parasmittina raigii , and Scrupocellaria scruposa .…”
Section: Discussionmentioning
confidence: 99%
“…Among the newly added species, C. roulei is a Mediterranean endemic, whereas Phallusia nigra and Herdmania momus are considered non-indigenous species (NIS) of circum(sub)tropical and Indo-pacific origin, respectively (Gerovasileiou et al 2016); both species have been probably introduced through shipping (Galil et al 2016). Another three species, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Bilecenoğlu and Taşkavak (1999) reported that a school of this species (as P. vanicolensis) was observed in a cave of the coast of Antalya, Turkey and even though, the divers forced them to leave the cave during daytime, the schools tended to stay inside. In a recent study, P. rhomboidea was observed in s mall mixed schools along with Sargocentron rubrum and Apogon imberbis in small caves of Kastelorizo Island (Greece), close to Kaş, southern Turkey (Gerovasileiou et al 2016). …”
Section: Resultsmentioning
confidence: 99%